Strategies of water flow treatment of Paringin Pit Lake to meet wastewater discharge compliance - Suhernomo Suhernomo; Luthfi Fatah; Akhmad Rizalli Saidy; Bambang Joko Priatmadi; Ihsan Noor; Didik Triwibowo (Brawijaya University, 2023)
Coal mining by the open-pit mining method creates the formation of a pit lake. The ex-mining site, over time, was gradually filled with contaminated water and must be returned to the water quality standard of compliance level. With proper treatment, the pit lakes have the potential for several benefits and subsequent uses. This study aimed to analyze the existing condition of the Paringin Pit Lake at South Kalimantan by identifying the quality of the water flow, and it is compliance with the parameter threshold values. The results showed that the pit lake water management had been carried out supported by good management of the catchment area and was indicated the stable category by geology technical study. The success of its revegetation processed in the area was shown by an erosion study in which the result was a very low-level category. No less important is the management of runoff water both in the quantity of water balance control and consistent water quality treatment to meet the quality standard values that have been set. The Paringin Pit Lake water management strategy is a form of activity that demonstrates compliance with good and responsible mining principles to support sustainable development that can serve as a good reference and example for other mining activities in terms of mine closure preparation.